Store brand proneness: effects of perceived risks, quality and familiarity - Wee Yu Ghee; Yap Sheau-Fen; Leong Sun-May (Elsevier, 2012)
While international retailers engage in the active promotion of store brands, consumers from Asia–Pacific markets remain resistant to purchasing store brands despite the intensification of promotional efforts. This study extends previous store brand research by: (1) determining the mediating role of perceived quality within a model of the antecedents and consequences of quality; and (2) assessing the extent to which age moderates the strength of relationships posited in the model. The model was tested in a retail store brand context using a quota sample of 220 shoppers and a cross-sectional survey. Empirical results suggest that performance risk, physical risk, and familiarity have significant effects on both perceived quality and purchase intention. Familiarity had the strongest total effect on perceived quality and store brand proneness in a collectivistic culture such as Malaysia and its effect on store brand proneness was partially mediated by perceived quality. Lastly, the finding that age moderates the impact of performance risk, physical risk, familiarity and perceived quality on store brand proneness provides insights into store brand management.